Pendampingan dan Pelatihan TOEFL Test Sebagai Kontribusi dalam Kegiatan Perpustakaan Seru pada Dinas Perpustakaan dan Arsip Kabupaten Gresik - Dewi, Risma Kartika; Sriwulandari, Novi; Yaqin, Muhammad Ainul; Ihsan, Mas Darul; Trisnantasari, Ika; Agustin, Faradilla (Community: Jurnal Pengabdian Kepada Masyarakat, 2021)
TOEFL Training and Tests were held as a contribution to the "Seru Library" activities at the District Library and Archives Office. Gresik, where this activity is based on the fact that we want to introduce TOEFL to high school students of the same level. "Perpus Seru" is an activity held by the Gresik Regency Library and Archives Service where the event presented is by bringing in volunteer resource persons who want to share their knowledge with the public. Class XII of Senior High School students is the target of this activity. The students are able to gain some advantages from the literacy class because TOEFL (Test of English as a Foreign Language) will be used as one of the graduation requirements from university. The methods of this community service activity are lectures, discussions and TOEFL (Test of English as a Foreign Language) exercises. After participating in this activity, literacy class participants are expected to: 1) know about TOEFL (Test of English as a Foreign Language); 2) be able to understand various questions in TOEFL (Test of English as a Foreign Language); 3) be able to understand various tips and tricks for taking the TOEFL (Test of English as a Foreign Language); and 4) be able to do TOEFL (Test of English as a Foreign Language).